2020
DOI: 10.1111/imb.12665
|View full text |Cite
|
Sign up to set email alerts
|

Two fatty acid synthase genes from the integument contribute to cuticular hydrocarbon biosynthesis and cuticle permeability in Locusta migratoria

Abstract: Lipids of the insect cuticle have important roles in resistance against the arid environment and invasion of foreign substances. Fatty acid synthase (FAS) is an important enzyme of the insect lipid synthesis pathway. In the present study, we identified three FAS genes from transcriptome data of the migratory locust, Locusta migratoria, based on bioinformatics analyses. Among them, two FAS genes (LmFAS1 and LmFAS3) are highly expressed in the integument of fifth instar nymphs. Suppression of LmFAS1 and LmFAS3 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…In the model organism C. elegans , silencing FASN-1 at the larval stage ceases normal development and juvenile nematodes are not able to reach adulthood successfully [ 31 ]. In a recent study, Yang et al [ 32 ] reported that the injection of dsLmFAS1 and dsLmFAS3 caused about 80% mortality in Locusta migratoria . Therefore, FAS may be essential for insect development.…”
Section: Discussionmentioning
confidence: 99%
“…In the model organism C. elegans , silencing FASN-1 at the larval stage ceases normal development and juvenile nematodes are not able to reach adulthood successfully [ 31 ]. In a recent study, Yang et al [ 32 ] reported that the injection of dsLmFAS1 and dsLmFAS3 caused about 80% mortality in Locusta migratoria . Therefore, FAS may be essential for insect development.…”
Section: Discussionmentioning
confidence: 99%
“…More information on the genes such as estimated evolutionary rates based on orthogroup and phyletic profiles can be found in Table S1 in the supplementary information as well as more genes with an impact on CHC profiles whose function could not be assigned to a particular step in the CHC biosynthesis pathway. the mb-CHCs detected in this species, while both in-and decreasing the amounts of different n-alkane compounds with no apparent pattern (Yang et al 2020). Two further putative FAS genes have been identified in the genome of the seaweed fly Coelopa frigida, though their direct impact on CHC variation has not been investigated as of yet (Berdan et al 2019).…”
Section: Fatty Acid Synthase (Fas)mentioning
confidence: 90%
“…Free fatty acids were determined from the ds GFP- and ds DcGSK3 -treated samples according to the protocol reported by Yang et al with minor modifications [ 55 ]. Briefly, 40 D. citri were added to a 1.5 mL centrifugation tube and 1 mL of extracting solution was added before homogenizing on ice.…”
Section: Methodsmentioning
confidence: 99%